(untitled) (Research, Society and Development, 2021)
The Xylocopa spp. bees are present in the most diverse ecosystems and usually have a solitary habit. These bees build their nests in trunks of dead wood, dry and in a preliminary stage of decomposition and are the most efficient pollinating agents in the pollination of passion fruit (Passiflora edulis f. flavicarpa Deg.). The knowledge of the nesting habit in their (natural) habitat is a fundamental element for the use of rational hives of these bees in P. edulis plantations. This work aimed to analyze the nesting behavior of Xylocopa spp taking into account: magnetic nesting orientation (cardinal and collateral points), substrate used, substrate diameter, daylight diameter and nest height in relation to the ground. The research was conducted in properties located in the municipality of Picuí, micro-region of the Seridó Oriental Paraibano. An Analysis of Variance (ANOVA) was performed and the mean compared by Tukey’s test (p ≤ 0.05). In this microregion, two species of Xylocopa were identified: X. (Neoxylocopa) grisescens Lepeletier, 1841 and X. (Neoxylocopa) cearenses Ducke, 1910). These species showed nesting habits in cashew (Annacardium occidentale), umburana (Commiphora leptophloeos), mulungú (Erythrina mulungu) and cowberry (Tabebuia caraiba). These bees have a nesting preference towards the southwestern (SW) collateral point.